1972
DOI: 10.1080/00207597208246604
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Cognitive Styles in Chinese and American Children

Abstract: Une épreuve adaptée du Sigel Cognitive Style Test a été appliquée à 316 élèves américains et 221 élèves chinois (Taiwan) du quatrième et cinquième degré de l'école élémentaire. Il était supposé que, par rapport à leurs condisciples chinois, les écoliers américains obtiendraient des résultats 1) supérieurs pour le style descriptif‐analytique; 2) inférieurs pour le style descriptif‐global; 5) inférieurs pour le mode relation‐contexte; 4) supérieurs pour le style inférence‐catégorie. Les résultats ont confirmé le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
204
2
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(223 citation statements)
references
References 7 publications
12
204
2
5
Order By: Relevance
“…Even though many cultural differences are flexible to some degree, they appear to be acquired early in life (Chiu, 1972;Fernald & Morikawa, 1993;Imai & Gentner, 1997) and operate pervasively across a number of testing environments and tasks. Different information-processing biases across cultures could result from environmental affordances present in one's daily environment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many cultural differences are flexible to some degree, they appear to be acquired early in life (Chiu, 1972;Fernald & Morikawa, 1993;Imai & Gentner, 1997) and operate pervasively across a number of testing environments and tasks. Different information-processing biases across cultures could result from environmental affordances present in one's daily environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ji, Peng, and Nisbett (1999) found that Chinese participants were more capable of detecting covariation among arbitrary events than Americans, but more field dependent as indicated by the fact that they were more influenced by the position of the frame when judging the verticality of the rod in the Rod and Frame Test. In addition, Westerners learn arbitrary categories more readily using rules (Norenzayan, Nisbett, Smith, & Kim, 1999), make more use of categories for purposes of induction than do Asians (Choi, Nisbett, & Smith, 1997), are more likely to use categories for purposes of grouping objects than to use relationships among the objects (Chiu, 1972;Norenzayan, et al, 1999), and are more willing to set aside their preconceptions when these are contradicted by logical argument .…”
Section: Holistic Vs Analytic Epistemologiesmentioning
confidence: 99%
“…Consider, for example, how cultural systems vary in their emphasis on individuals and relations. Although Westerners tend to favor taxonomic groupings and to focus on individuated entities isolated from context, non-Westerners tend to group objects in a relational-contextual manner ('mothers take care of babies and go together') and to focus on holistic systems of entities embedded in context [27,31,[44][45][46][47]. Relational approaches may support teleological responses precisely because they highlight ecological affordances and relations.…”
Section: Are Clouds 'For' Raining?mentioning
confidence: 99%